Tensor Interpolation - Ouahidi, Salma; Sadaka, Rachid (Numerical algorithms, 2025)
In this paper, we develop a new Lagrange tensor interpolation. We define tensorial jordanisation which gives us a practical method to calculate the coefficients of our tensor interpolating polynomial. Unlike what happens in the case of matrices where the product is simpler, there are multiple tensorial products; we use the T -product and develop a new product which is most suitable for our work, we determine the coefficients of our interpolating polynomial as well as give the expression of the Langrange tensor interpolating polynomial. Furthermore, we will give examples of the effectiveness of this method in interpolating tensorial functions.